Sociological Explanation of the Role of Counseling and Cultural Centers in Iranian Young Athletes\' Unprofessional Behaviors and Lawlessness - Ali Ghanbari Barzian; Mostafa Zahirinia (Iranian Journal of Educational Research)
Objective: The primary objective of the current research was to carry out a sociological analysis regarding the level of adherence to professional sports ethics within Iranian society. Methods: The research methodology entailed conducting investigations in nine cities and across seven sports disciplines, with a sample size of 1765 players in the year 2019. Additionally, fifty exploratory interviews were conducted with experts in the field. Results: The findings of the research indicate that the nonexistence of political programs, coupled with deficiencies in the implementation, supervision, and monitoring within the structures and systems of club ownership, serve as the underlying cause for the noncompliance of young athletes with rules, regulations, and professional standards. Moreover, the inefficiency in the field of education, as well as the lack of knowledge and awareness pertaining to professional and ethical charters and regulations, are among the prominent factors contributing to the lawlessness exhibited by young athletes. As part of the solutions, expediting the process of privatization, mandating the teaching of ethical codes in all fields, formulating and consolidating rules and regulations for the legal control and supervision of sports publications, issuing fan cards, enforcing stringent regulations, and implementing bans in cases of abnormality can all contribute to the enhancement of the sporting environment and the promotion of lawfulness within sports. The research data demonstrate a direct correlation between seeking counseling services and the incidence of unprofessional and illicit conduct. Conclusions: The findings generally show that counseling centers can play a decisive role in preventing unprofessional and illicit behaviors of athletes.